The Inferiority Complex Constructed by the Dominant Power in Rhys’ Wide Sargasso Sea (1966): Postcolonial Analysis - Indiwara Pandu Widyaningrum (Indonesian Journal of English Language Studies (IJELS), 2021)
This study focuses on the construction of identity shaped by the dominant class. Jean Rhys’ Wide Sargasso Sea  portrays the complexity of identity in the figure of Creole woman, Antoinette, for belonging to neither the Jamaican society nor the European. Using interpretive qualitative approach as its method, this study applies the theory of power and knowledge to reveal the imbalance power relation between center and marginalized. The result of analysis shows that both Jamaican society and Rochester have the contribution in shaping the inferiority complex to Antoinette. The representation of madwoman in Antoinette implies the constructed truth framed by the dominant class. As a result of the inferiority complex, the dependency of the inferior on the superior grows which consolidates the domination of power. Under this situation, the dominant power legitimates their authority to represent others as well as to control the marginalized side. Thus, this study intends to raise the awareness of any kind of oppression which limits people to have a voice.